Growth and Productivity of Wheat Varieties in an Agrisilviculture System - Puri, Sunil; Sao, Bhawana; Swamy, S.L. (Indian Journal of Agroforestry, 2020)
Field experiment was conducted to investigate the growth and productivity of wheat-varieties under Ceiba pentandra (L.) Gaertn. based agrisilviculture system. The system comprises of three tree spacings (4 x 4m, 4 x 6m and 4 x 8m) and four varieties of wheat (Sujata, Lok-1, Kanchan and GW-174). The experiment was laid out in a factorial randomized block design with five replications. The results revealed that the plant population, number of tillers, root-shoot biomass, plant height and number of effective tillers were maximum in the sole crop (control). Grain yield was highest in Kanchan (dwarf) variety. The order of yield reduction in different varieties was: Sujata (34.5 %) > Lok-1 (17.6 %) > GW-174 (14.5 %) when compared with Kanchan variety. Higher grain yield (30.2 q/ha) was obtained in 4 x 8 m tree spacing, while in other two tree spacings the grain yield was 27.9 q/ ha (4 x 6m) and 26.3 q/ha (4 x 4 m). Grain yield and growth parameters also varied with distance from the tree base. Grain yield was lowest near the tree base. The growth and development of crop was better as the distance from the tree base increased. It is recommended that Kanchan variety of wheat be grown under Ceiba pentandra tree system.